Inclusivité linguistique : une quête de clarté et de précision conceptuelle - Paweł Golda; Natalia Żywicka (Studia Linguistica)
The objective of this paper is to conduct a comprehensive review of synonymous or quasi-synonymous terms related to the phenomenon of inclusive language. The paper defines the concept of linguistic inclusivity, enumerating the analysed terms, and aims to clarify the reasons for the proliferation of terminologies. Additionally, it examines eight techniques designed to avoid the use of generic masculine expressions. The paper takes an analytical approach to characterize nine terms that frequently appear in linguistic literature, identifying which practices may be encompassed within the specified terms.